2017
DOI: 10.18203/2349-3291.ijcp20175581
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haematological profile of children with sickle cell anaemia admitted to a rural medical college of Chhattisgarh, India

Abstract: Background: Sickle cell disease (SCD) is the most common single gene disorder resulting in hemolytic anemia. Aim of the study was to describe the clinico-haematological profile of children with sickle cell anaemia admitted to Paediatric ward/PICU with any acute clinical event and to find out the association between high HbF level, frequency of crises episodes and requirement of blood transfusion in sickle cell anemia. Methods: Hospital based descriptive study. Retrospective data analysis was done from medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
4
4
0
Order By: Relevance
“…In the present study, about half (50.8%) of the children with SCD admitted were of age group  5 years which was consistent with reports by George & Opara [15] Faruk et al [19] and Nayak et al [21] in a previous study in Port Harcourt, Zaria in Nigeria and India respectively. Ikefuna and Emodi [16] in Enugu, Nigeria reported age group 1-5 years as the commonest age group admitted whereas Jain et al [3] in India reported 1-< 3 years as the commonest age group implicated.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, about half (50.8%) of the children with SCD admitted were of age group  5 years which was consistent with reports by George & Opara [15] Faruk et al [19] and Nayak et al [21] in a previous study in Port Harcourt, Zaria in Nigeria and India respectively. Ikefuna and Emodi [16] in Enugu, Nigeria reported age group 1-5 years as the commonest age group admitted whereas Jain et al [3] in India reported 1-< 3 years as the commonest age group implicated.…”
Section: Discussionsupporting
confidence: 92%
“…Males predominated in the present study as similarly documented in other studies in Nigeria [10,[15][16][17]19,20], Malawi, [14] India [3,21] Iraq [18] and Barbados [22]. Although SCD is an autosomal recessive disorder and as such not related to gender, Gladwin et al [23] and Ilesanmi [24] in their studies showed that nitric oxide was found more in females than males during both steady state and crisis which thus indicates that males could be more prone to crisis and attendant complications.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Mpalampa et al 16 considering the mean HbF cut-off as 10%, in 216 sickle cell anemia patients observed a strong negative correlation of HbF levels with the total number of transfusions (r = − 0.181, P: 0.004), hospitalisations rate (r = − 0.173, P: 0.006), and significant positive correlation with the age at diagnosis (r = 0.151, P: 0.013) 16 . In the Indian context, Nayak et al 17 studied 60 sickle cell anemia patients and observed fewer episodes of painful crises in children with high baseline HbF level as compared to children with low HbF level 17 . Correspondingly in our study as well, the mean age of diagnosis among 100 SCA patients was found to be 6.3 ± 5.2 years which is very much delayed as compared to the patient cohort studied by Mpalampa et al 16 .…”
Section: Discussionmentioning
confidence: 99%